Pengaruh Budaya Konsumerisme Terhadap Masyarakat Kota - Tedy Wiraseptya; Melisa Suardi (Majalah Ilmiah UPI YPTK, 2019)
Urban society as modern society does not only consume functional basic needs to survive. But fulfilling needs that are becoming a desire of urban society. The birth of the culture of consumerism is currently making rapid changes to the city community. However, not all urban communities accept this change. therefore, it is not uncommon to fight arguments and violence resulting from changes in consumerism. This culture of consumerism is motivated by the emergence of a period of capitalism which is carried by liberalism. The emergence of a culture of consumerism has a positive and negative impact. Has a positive impact when the employment field increases, the birth of new technology and others. The negative is when hedonism, consumerism, capitalism, and others arise